Peningkatan Kelarutan Granul Instan Ekstrak Daun Sirih Merah (Piper crocatum) Dengan Penambahan β-Siklodekstrin: Formulasi Dan Karakterisasi : Increasing The Solubility Of Instant Granules Of Red Betel Leaf Extract (Piper crocatum) With The Addition Of β -Cyclodextrin: Formulation And Characterization - Mia Arifka; Dwi Retno Sari; Aprilia Anel Putri (JURNAL FARMASI DAN MAKANAN, 2025)
Red betel leaves contain a high amount of secondary metabolites such as flavonoids, alkaloids, and essential oils that has been used as an anticancer, antidiabetic, and antiseptic. Granule formulation is one of the strategies to enhance the practicality and interest of the public in consuming herbal medicines; however, the dissolution time of instant granule preparations is relatively long. This study aims to improve the solubility of red betel leaf extract by adding β-cyclodextrin, so that the granules produced can dissolve well. The methods used in this study include the extraction of simplicia through maceration using ethanol 70%. The preparation of the complex between the extract and β-cyclodextrin used the spray drying method with ratios of 1:1, 1:2, and 1:3, and tested the solubility of the total flavonoids in the extract. Granule production was carried out using the wet granulation method. The extraction results yielded a yield of 10.92%. The results of the complex formation showed an increase in the solubility of total flavonoids from the extract of 14.221% (F1), 26.646% (F2), and 29.041% (F3), indicating that the addition of the β-cyclodextrin can enhance the solubility of the red betel extract through complex formation. The results of the physical properties test of the granules showed good results after storage for 28 days. The granule dissolution time test results showed a good dissolution time of, less than 5 minutes.